Transient Fluctuation Suppression Strategy for MMC Flexible DC Systems Based on Gain-Varying Extended Disturbance Observer - Huanruo Qi; Yilong Kang; Xiaojv Lv; Ziwen Liu; Xiangyang Yan; Fang Guo (IEEE Access)
Modular Multilevel Converter Based High Voltage Direct Current (MMC-HVDC) system is an important technical means to realize grid connection and transmission of new energy. When the external disturbance occurs in the MMC-HVDC system, the submodule capacitance voltages suffer instant impact due to the mutual coupling in the MMC, which causes transient fluctuation and unstable operation of the system. In order to suppress the impact of external disturbance on the internal submodule capacitance voltage transient fluctuations of MMC-HVDC system, the transient fluctuation suppression strategy based on gain-varying extended disturbance observer is proposed in this paper. Firstly, the transient response characteristic equation of the submodule capacitor voltage fluctuation component for MMC-HVDC system is constructed, which reveals the relation between the external output and internal dynamic response of the system. Next, a gain-varying extended disturbance observer is proposed to effectively observe the time-varying disturbance current components in the system, and the corresponding submodule capacitor voltage transient fluctuation suppression strategy is then proposed to improve the dynamic response performance and anti-interference ability of the MMC-HVDC system under different disturbances. The simulation model of MMC-HVDC system is built on PSCAD/EMTDC platform, and the validity and correctness of the proposed method are verified by several simulation tests.